2018
DOI: 10.1002/dvdy.24683
|View full text |Cite
|
Sign up to set email alerts
|

Pparα deficiency inhibits the proliferation of neuronal and glial precursors in the zebrafish central nervous system

Abstract: Background: Many molecules and signaling pathways involved in neural development play a role in neurodegenerative diseases and brain tumor progression. Peroxisome proliferator‐activated receptor (PPAR) proteins regulate the differentiation of tissues and the progression of many diseases. However, the role of these proteins in neural development is unclear. Results: We examined the function of Pparα in the neural development of zebrafish. Two duplicate paralogs for mammalian PPARA/Ppara, namely pparaa and ppara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…The zebrafish (Danio rerio) has been regarded as a well-accepted animal model and widely used in the studies of cellular energy metabolism (Den Broeder et al 2015;Li et al 2017;Yang et al 2017;Yang et al 2018;Lu et al 2019). Two paralogues of PPARα have been defined in zebrafish on the basis of their similarity: pparaa (GenBank: NM 0 011 61333.1) and pparab (GenBank: NM 0 011 02567.1) (Hsieh et al 2018). We found that zebrafish predominantly express the pparab subtype.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The zebrafish (Danio rerio) has been regarded as a well-accepted animal model and widely used in the studies of cellular energy metabolism (Den Broeder et al 2015;Li et al 2017;Yang et al 2017;Yang et al 2018;Lu et al 2019). Two paralogues of PPARα have been defined in zebrafish on the basis of their similarity: pparaa (GenBank: NM 0 011 61333.1) and pparab (GenBank: NM 0 011 02567.1) (Hsieh et al 2018). We found that zebrafish predominantly express the pparab subtype.…”
Section: Introductionmentioning
confidence: 86%
“…Two paralogues of PPARα have been defined in zebrafish on the basis of their similarity: pparaa (GenBank: NM_0 011 61333.1) and pparab (GenBank: NM_0 011 02567.1) (Hsieh et al . 2018). We found that zebrafish predominantly express the pparab subtype.…”
Section: Introductionmentioning
confidence: 99%
“…Two duplicate paralogs of mammalian PPARA namely, Pparαa and Pparαb are present in the zebrafish genome. Both Pparαa and Pparαb are essential regulators of the proliferation of neuronal and glial precursors in zebrafish embryos (Hsieh et al 2018). Based on our findings that trim46a is implicated in zebrafish neurogenesis, further study of its relevance to Pparαa and Pparαb would be an interesting topic.…”
Section: Discussionmentioning
confidence: 99%
“…S5a and b). The orthologs of mammalian PPARα regulate the formation of neurons and glial cells in the zebrafish [74] . In vitro studies showed that PPARα is expressed in neural stem cells, and that some PPARα target genes modulate cell proliferation [ 22 , 75 ].…”
Section: Discussionmentioning
confidence: 99%